Elbow MRI Findings Do Not Correlate With Future Placement on the Disabled List in Asymptomatic Professional Baseball Pitchers. (May 2017) - Gutierrez, Nicholas M.; Granville, Christopher; Kaplan, Lee; Baraga, Michael; Jose, Jean
Background: Injury rates among professional baseball players may reach as high as 5.8 per 1000 encounters, with pitchers being most vulnerable on account of the excessive biomechanical load on the upper extremity during the throwing motion. Anatomically, the shoulder is the most common site of pitching-related injury, accounting for 30.7% of injuries, closely followed by the elbow at 26.3%. Characteristic valgus loading imparts a predictable constellation of stresses on the joint, including medial tension, lateral compression, and posterior medial shearing. The degenerative cohort of tissue changes that result are readily detected on magnetic resonance imaging (MRI). It is not yet known whether such findings predict future placement on the disabled list (DL) in asymptomatic Major League pitchers. Hypothesis: Abnormal soft tissue and osseous changes detected on MRI of the throwing elbow in asymptomatic professional pitchers will impart an increased risk of subsequent transfer to the DL in the season after MRI. Study Design: Retrospective cohort study. Level of Evidence: Level 3. Methods: The study aimed to examine a potential association between the total number of innings pitched (approximate lifetime valgus load) and the typical MRI degenerative changes, hypothesizing a rejection of the null hypothesis. A total of 26 asymptomatic professional pitchers from a single Major League Baseball (MLB) organization and its various minor league affiliates underwent MRI of their dominant elbow from 2003 to 2013 as a condition of their contract signing or trade. Twenty-one of those pitchers played at the Major League level while 5 played with the team's minor league affiliates including both the AA and AAA levels. Asymptomatic was defined as no related stints on the DL due to elbow injury in the 2 seasons prior to MRI. A fellowship-trained musculoskeletal radiologist reevaluated the studies after being blinded to patient name, injury history, and baseball history. A second investigator collected demographic data; this included total career number of innings pitched and any subsequent DL reports for each subject while remaining blinded to the MRI results. Results: The mean age at the time of MRI was 29.6 years (range, 19-39 years). The mean number of innings pitched was 1111.7. Of the 26 pitchers, 13 had scar remodeling of the anterior bundle of the ulnar collateral ligament (UCL). Of those, 4 had partial-thickness tears of the anterior bundle of the UCL, ranging from 10% to 90% of the total thickness. Twelve had articular cartilage loss within the posteromedial margin of the ulnohumeral joint, and 12 had posteromedial olecranon marginal osteophytes. Seven pitchers had degeneration of the common extensor tendon origin, 10 had degeneration of the flexor pronator mass, 9 had insertional triceps tendinosis, 2 had enthesopathic spurs at the sublime tubercle, 3 had osteochondral intra-articular bodies, and 2 subjects had joint effusions. In the year after MRI, 6 pitchers were placed on the DL for elbow-related injuries. There was no robust correlation between any single MRI finding and subsequent transfer to the DL, and no statistically significant correlation between number of innings pitched and MRI findings, although some trends were observed for both. Conclusion: MRI findings in asymptomatic MLB pitchers were not associated with placement on the DL within the subsequent year. While a trend was observed with olecranon osteophytes and subsequent DL placement ( P = 0.07), this finding did not reach statistical significance. Furthermore, there was no robust correlation between the number of innings pitched with the presence of any of the aforementioned degenerative changes on MRI. Clinical Relevance: The characteristic structural transformation that occurs in the throwing elbow of professional pitchers is predictable and readily detectable on MRI. However, this study suggests that these changes are not predictive of near-term placement on the DL in those who are asymptomatic. Abnormal findings on MRI, even high-grade partial UCL tears, do not correlate with near-term placement on the DL, mitigating their potential negative impact on signing decisions.